2017
DOI: 10.1016/j.ekir.2017.06.061
|View full text |Cite
|
Sign up to set email alerts
|

117 a Prospective Study of Acute Kidney Injury in Tropical Acute Febrile Illness in West Pahang, Malaysia

Abstract: medical records in the hospital information system. Results were analyzed using SPSS version 23. Results: A total of 78 patients fulfilled the inclusion criteria. The mean age was 52.4 and predominantly male (66.6%). Comorbidities identified in this cohort were diabetes mellitus, hypertension and ischemic heart disease bringing to a total of 52.5%, followed by patients with preexisting CKD stage 2 to 4 (23%), retroviral disease (RVD) (7.7%) and there were 2 patients with underlying malignancy. 13 patients (16.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Three studies of TAFI-associated AKI conducted in India between 2010 and 2018 reported a prevalence between 28–54% using either RIFLE or KDIGO criteria [ 4 , 30 , 31 ]. One study from Malaysia in 2017 reported TAFI-associated AKI with a prevalence of 41.1%, using KDIGO [ 32 ]. The wide range of reported AKI prevalence was due to the different AKI criteria being used, as well as the different etiology of AKI in these places.…”
Section: Discussionmentioning
confidence: 99%
“…Three studies of TAFI-associated AKI conducted in India between 2010 and 2018 reported a prevalence between 28–54% using either RIFLE or KDIGO criteria [ 4 , 30 , 31 ]. One study from Malaysia in 2017 reported TAFI-associated AKI with a prevalence of 41.1%, using KDIGO [ 32 ]. The wide range of reported AKI prevalence was due to the different AKI criteria being used, as well as the different etiology of AKI in these places.…”
Section: Discussionmentioning
confidence: 99%